2021
DOI: 10.1016/j.jvsv.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, clinical characteristics and outcomes of deep venous Thrombosis in patients with COVID-19 attending the emergency department: Results of the UMC-19-S8

Abstract: on behalf of the Spanish Investigators on Emergency Situations TeAm (SIESTA) network** Background and importance A higher incidence of venous thromboembolism [both pulmonary embolism and deep vein thrombosis (DVT)] in patients with coronavirus disease 2019 (COVID-19) has been described. But little is known about the true frequency of DVT in patients who attend emergency department (ED) and are diagnosed with COVID-19.Objective We investigated the incidence, risk factors, clinical characteristics and outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…10 In one study DVT as the presenting feature of COVID-19 was found to be 1.5% and was associated with worse prognosis. 11 Infection induced inflammatory changes have been considered as cause of VTE. 11,12,13 So, the aim of the study is to know the proportion of cases of DVT with concomitant COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In one study DVT as the presenting feature of COVID-19 was found to be 1.5% and was associated with worse prognosis. 11 Infection induced inflammatory changes have been considered as cause of VTE. 11,12,13 So, the aim of the study is to know the proportion of cases of DVT with concomitant COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…11 Infection induced inflammatory changes have been considered as cause of VTE. 11,12,13 So, the aim of the study is to know the proportion of cases of DVT with concomitant COVID-19. The study also aims to know any major differences between DVT patients with and without COVID-19 status.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the SIESTA network has provided one of the largest series published worldwide for some entities. This incentivized top journals of many specialties [14–17] as well, obviously, as the leading journals in the field of emergency medicine [18,19] to published research led by emergency medicine physicians.…”
Section: Third Fact: the Siesta Network Also Provided Key Information...mentioning
confidence: 99%